Pemanenan Getah Karet (Hevea brasiliensis Muell. Arg) dan Penentuan Kadar Karet Kering (KKK) dengan Variasi Temperatur Pengovenan di PT. Djambi Waras Jujuhan Kabupaten Bungo, Jambi - Pusari, Dewi; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Rubber tree (Hevea brasiliensis Muell.Arg) is one of the prime commodities in Indonesia for export and domestic demand and industrial raw material purposes. The quality of raw rubber material which is exported to abroad  is determined  through the harvesting process and also postharves processing material rubber. The good quality of rubber must be exempted from water contaminants or from other contaminant. The quality of rubber can be determined by analysis of Rubber’s Dry Content.  The perpose of this research is to analyze the condition Rubber’ Dry Content with temperatur of 150oC, 160oC and 170oC in PT Djambi  Waras Jujuhan. The observation result of the physical treatment shows in the influence of  temperatur toward Rubber’s Dry Content. Tempereture of 160oC shows ripennes and the      best physical structure and also has Rubber’s Dry Content appropriate with the standard than    two others temperature.